Hypergraph extensions of the Erdős-Gallai Theorem - Győri, Ervin; Katona, Gyula Y.; Lemons, Nathan (European journal of combinatorics, 2016)
We extend the Erdős-Gallai Theorem for Berge paths in r-uniform hypergraphs. We also find the extremal hypergraphs avoiding t-tight paths of a given length and consider this extremal problem for other definitions of paths in hypergraphs.